Influence of alkali on the drying shrinkage of cement pastes - Bettencourt Ribeiro António; Custódio João; Real Sofia (MATEC Web of Conferences, 2025)
Concrete shrinkage remains a relevant topic of study due to the increased use of high- performance concrete. Understanding shrinkage mechanisms is essential for developing non-shrinking concrete and reducing cracking problems. During concrete curing, substantial quantities of alkalis dissolve in the pore solution, and their influence on shrinkage is not fully understood. This paper gives further insight into the role of the alkalis, by monitoring the length changes and mass variations of hardened cement pastes with pore structures saturated with solutions containing potassium hydroxide (KOH) in the presence or absence of a shrinkage reducing admixture (SRA). The method used does not include the effects of the alkalis on the formation of the pore structure, but it has the advantage of isolating the individual influence of KOH and SRA on shrinkage. The results are consistent with a reduction of shrinkage for increased alkali concentrations and suggest an explanation for contradictory experimental results reported in the literature.